PERANCANGAN CONVENTION CENTRE DENGAN PENDEKATAN ARSITEKTUR KONTEMPORER DI KOTA PALANGKA RAYA - Irawan, Satria Khabib Argiansyah Adi; Hamidah, Noor; Fransisco, Theo; Rosalia, Alderina; Usop, Joni Wahyubuana (Fakultas Teknik Universitas Palangka Raya, 2025)
Palangka Raya City, as the capital of Central Kalimantan Province, plays a strategic role as a center of government, economic, social, and cultural activities. Along with urban development and the increasing demand for regional, national, and international-scale events, a representative convention facility is required to accommodate various activities such as conferences, seminars, exhibitions, and public events. However, to date, Palangka Raya does not yet have a Convention Centre that adequately meets standards in terms of capacity, spatial flexibility, and architectural quality. This Final Project aims to design a Convention Centre in Palangka Raya City using a contemporary architectural approach that addresses functional requirements, aesthetic values, and building sustainability. The design methodology applied includes descriptive methods to examine existing conditions and urban needs, comparative methods through precedent studies of similar buildings, data analysis related to site conditions, spatial programming, and technical standards, as well as the BASIC design method (Brief, Analysis, Synthesis, Implementation, and Concept). The contemporary architectural approach is implemented through spatial flexibility, integration of modern technology, the use of innovative materials, and dynamic massing that responds to the local context. The result of this project is a Convention Centre design concept featuring main facilities such as an auditorium, exhibition hall, and meeting rooms with a flexible multi-layout hall system. This design is expected to serve as a representative venue for convention and exhibition activities, support the growth of the creative economy and tourism sector, and become a new landmark contributing to the development and urban image of Palangka Raya City.